Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/hep.22698
|View full text |Cite
|
Sign up to set email alerts
|

Allelic imbalances and homozygous deletion on 8p23.2 for stepwise progression of hepatocarcinogenesis

Abstract: Early hepatocellular carcinoma (eHCC) originates from the hepatocytes of chronic liver disease and develops into classical hepatocellular carcinoma (HCC). To identify sequential genetic changes in multistep hepatocarcinogenesis, we analyzed molecular karyotypes using oligonucleotide genotyping 50K arrays. First, 1q21.3-44 gain and loss of heterozygosity (LOH) on 1p36.21-36.32 and 17p13.1-13.3 were frequently observed in eHCC, but not in chronic liver diseases, suggesting that such chromosomal aberrations are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 85 publications
(44 reference statements)
6
71
0
Order By: Relevance
“…We examined whether DACH1 expression affected TGF-β signaling in glioma cells. Induced DACH1 expression reduced the proliferation of the U-373MG cells, which are widely used as a cell model for analyzing TGF-β signaling (19), and repressed TGF-β3-stimulated (CAGA) 9 -and p800-luciferase activity ( Fig. S5 A-C).…”
Section: Dach1 Inhibits Formation Of Tumor-initiating Spheroids Of Glmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined whether DACH1 expression affected TGF-β signaling in glioma cells. Induced DACH1 expression reduced the proliferation of the U-373MG cells, which are widely used as a cell model for analyzing TGF-β signaling (19), and repressed TGF-β3-stimulated (CAGA) 9 -and p800-luciferase activity ( Fig. S5 A-C).…”
Section: Dach1 Inhibits Formation Of Tumor-initiating Spheroids Of Glmentioning
confidence: 99%
“…Genetic alterations of GBMs, including aberration of DNA copy number such as gene amplifications, loss of heterozygosity (LOH), and homozygous deletions, leads to activation of oncogenes and inactivation of tumor suppressor genes (1)(2)(3). DNA copy number analysis by single-nucleotide polymorphism (SNP) genotyping enables the high-resolution analysis of allelic DNA copy number and has been used to obtain a genome-wide view of DNA copy number alterations in human cancers (4)(5)(6)(7)(8)(9)(10). Particularly, pairwise analysis of normal and tumor DNAs is crucial in detecting homozygous deletion in clinical specimens, because infiltrating nontumorous cells are significant in GBMs.…”
mentioning
confidence: 99%
“…hsa-miR-486-5p is located on chromosome 8p11.21, which is one of the most frequent genomic deletion regions that contain potential tumor-suppressor genes in various types of tumors, such as NSCLC (14,15). hsa-miR-486-5p was first cloned from the fetal liver.…”
Section: Introductionmentioning
confidence: 99%
“…89 The 4-probes FISH has shown a sensitivity and speci-90 ficity of 86.7% and 95.4% respectively [18]. Recent 91 study has shown an improvement of the FISH assay by 92 incorporating new probes that target 4 different chro-93 mosomes (CDKN2A on 9p21, RREB1 on 6p25, MYC 94 on 8q24 and CCND1 on 11q13) with increased sensi- 95 tivity and specificity to 94% and 98% respectively [7]. 96 Although the FISH assay was introduced as a di-97 agnostic tool in the field of differential diagnosis of 98 melanoma fairly recently, the principle of developing 99 this assay was based on findings that existed over a 100 decade ago.…”
Section: Introductionmentioning
confidence: 99%
“…A 502 later study that sought to improve the sensitivity and 503 specificity of FISH assay for discriminating melanoma 504 from nevi has confirmed and included the 8q24 re-505 gion as one of four FISH targets with high discrimi-506 natory power to differentiate between melanoma and 507 benign nevi [7]. The most prominent gene in this re-508 gion is MYC, a proto-oncogene that encodes a nu-509 clear phosphoprotein transcription factor that plays a 510 role in different cellular processes, such as prolifer-511 ation, cell cycle progression, metabolism, differentia-512 tion and apoptosis [74] [95], ovary cancer [96], 588 and more common in the head and neck squamous cell 589 carcinoma (HNSCC) and correlates with poor prog-590 nosis [97,98]. In melanoma, a recent study of Tang 591 et al has reported that CSMD1 functions as a tumor 592 suppressor gene in melanoma cells.…”
mentioning
confidence: 99%